Magnetostatis Modes in Spin-Polarized Atomic Hydrogen - Lehtonen, Lauri (My University, 2023)
Magnetostatic modes are considered as a potential explanation for certain features of the electron spin resonance spectra observed in a gas of spin-polarized atomic hydrogen. The resonance spectra were measured in the Turku atomic hydrogen group. Magnetostatic modes are wave-like perturbative solutions of a disturbed oscillating magnetized medium described by the Walker equation. In this work, analytic solutions for the Walker equation are found in the experimentally relevant finite cylindrical geometry by imposing extra boundary conditions on the infinite cylinder. Unfortunately the model turns out to be unable to account for the observed modulations of the spectra, and the modulations it could produce are likely too narrow to be seen with the experimental apparatus

Tutkielmassa tutkitaan mahdollisuutta selittää eräitä spin-polaroidussa atomisessa vetykaasussa havaitun elektroni-spin-resonanssispektrin piirteitä magnetostaattisten värähtelymoodien avulla. Spektri on mitattu Turun atomisen vedyn ryhmässä; tutkielman kirjoittaja ei osallistunut mittaustyöhön. Magnetostaattiset värähtelymoodit ovat oskilloivan magneettisen aineen aaltomaisia häiriöratkaisuja, joita kuvataan Walkerin yhtälöllä. Tässä tutkielmassa Walkerin yhtälö ratkaistaan analyyttisesti kokeen äärellisessä sylinterissä lisäämällä reunaehtoja äärettömän sylinterin ratkaisuihin. Valitettavasti malli ei kykene selittämään spektrin havaittuja erikoispiirteitä, ja sen mahdolliset vaikutukset siihen lienevät terävyytensä takia koejärjestelmän ulottumattomissa.
Keywords: spin waves, atomic hydrogen, magnetostatic waves, elec- tron spin resonance, Walker’s equation, cold atoms.